2021
DOI: 10.1002/2211-5463.13173
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SUMO2 inhibits hepatocellular carcinoma cell proliferation, migration and invasion

Abstract: FEBS Open Bio (2021) ª 2021 The Authors. FEBS Open Bio published by John Wiley & Sons Ltd on behalf of Federation of European Biochemical Societies.SUMO2 promotes HCC progression J. Chen et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Additionally, literature cites SUMO2/3 as a pivotal agent driving colorectal cancer progression and oxaliplatin resistance by orchestrating the sumoylation modification of the DNA assembly constituent, Ku80 [56] . Recent revelations align with our experimental evidence, advocating that SUMO2 exerts a positive regulatory influence on hepatocellular carcinoma progression [ 57 , 58 ]. Concurrently, sumoylation modifications have been firmly established as regulators of CSC stemness [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, literature cites SUMO2/3 as a pivotal agent driving colorectal cancer progression and oxaliplatin resistance by orchestrating the sumoylation modification of the DNA assembly constituent, Ku80 [56] . Recent revelations align with our experimental evidence, advocating that SUMO2 exerts a positive regulatory influence on hepatocellular carcinoma progression [ 57 , 58 ]. Concurrently, sumoylation modifications have been firmly established as regulators of CSC stemness [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 66%
“…This observation aligns with a study by Chen et al, which demonstrated increased SUMO2 mRNA expression levels in liver cancer tissues compared with adjacent tissues. [34] Another previous study also showed that SUMO2 is upregulated and contributes to regulate the cell cycle in HCC. [35] Using siRNA to knock down SUMO2 expression, the authors showed that downregulation of SUMO2 may inhibit the proliferation, clone formation, and invasive ability of liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 20 In particular, higher expression of the genes involved in SUMOylation had been earlier detected as a pattern shared among patients with an accelerated progression of HCC. 21 To date, the upregulation of SUMO1, 22 SUMO2, 23 SAE1, 24 UBA2, 25 UBC9, 26 29 PIAS1, 30 PIAS2, 31 PIAS4, 32 , 33 SENP1, 34 36 SENP5, 37 SENP6, 38 , 39 and SENP7 40 in HCC and their value either as diagnostic or prognostic biomarkers have been described. Conversely, SENP2 expression is decreased in HCC and might play a role as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%